A sanção premial como instrumento de correção da atuação da empresa disfuncional no mercado - Machado, André Vinícius da Silva (2013)
The purpose of this dissertation is the demonstration that Company/enterprise in developing its activity and legitimate pursuit of profits, performs benefit materializing the idea of social function, are entitled to a different legal treatment, even in regard to the principle of material equality. Thus, the company entered into to the market environment, realizes the need for humanitarian achievements, social and distributional prestacional in return acts in pursuit of excellence and primacy to he market by adopting pratices not very convenient at the prestacional and welfare time, but grounded in interpretation of the law. Throughout the development of the survey was presented the model sanctions premials as a possible solution, a remedy against inequality, to conduct the company the imprint prestacionals practices to achieve a greater collective good: the common good.